RANCANG BANGUN DAN DESAIN SISTEM PENGATUR SUHU OTOMATIS UNTUK KANDANG AYAM CLOSE HOUSE BERBASIS ARDUINO - Joko Prasetiyo, Hendro; Kurniawan Hidayat, Syams (Journal of Computer Science and Technology (JCS-TECH), 2023)
ABSTRACT One of the problems experienced by chicken breeders is the number of chickens that die. One of the causes of the death of chickens is that the room temperature controller in the cage is still manual, so the owner sometimes forgets to turn on the fan and cooling of the cage when the temperature rises, so that the temperature in the cage does not match the temperature standard required by the chicken and causes the chicken to become stressed and then die. This research aims to make an automatic room temperature controller so that the temperature in the cage can be controlled automatically, and can reduce the death rate of chickens so that production levels increase. This system development method uses the waterfall method and the microcontroller uses Arduino. Based on testing the Arduino-Based Automatic Temperature Control Tool for Close House Chicken Coops has been functioning as expected. The DHT11 sensor is able to detect temperature and humidity well. The fan turns on when the temperature and humidity reach a predetermined temperature limit and the fan will automatically turn off when the temperature and humidity return to normal. Keywords: Arduino Microcontroller, DHT11 Sensor, Close House Chicken Coop